Urgensi Pembentukan Peraturan Daerah Kota Surabaya tentang Hunian yang Layak - Wiwik Aldewiyeh; Ida Wahyuliana (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
Decent housing is one of the important factors in ensuring social welfare and improving the quality of life of the community. The need for decent housing is very crucial in big cities, including Surabaya, where population growth and urbanization are very rapid. Although this right has been guaranteed by various national laws and regulations, one of which is regulated in Law Number 1 of 2011 concerning Housing and Residential Areas, there are still gaps in its implementation at the regional level. This article aims to discuss the urgency of establishing a Surabaya Regional Regulation (Perda) on decent housing. As a legal basis that regulates minimum standards for housing quality, access to basic infrastructure, and guarantees of security and comfort for Surabaya City residents. The establishment of this Perda is currently important to overcome the problem of inadequate housing, prevent the emergence of slums, and support the sustainable development of the city of Surabaya. In addition, this Perda is expected to be a solution to the challenges faced by the Surabaya City government in meeting the need for decent housing for all levels of society in the City of Surabaya.